Towards an evaluation and protection strategy for critical infrastructure - Gottschalk, Jason Howard (Rhodes University, Faculty of Science, Department of Computer Science, 2015)
Critical Infrastructure is often overlooked from an Information Security perspective as being of high importance to protect which may result in Critical Infrastructure being at risk to Cyber related attacks with potential dire consequences. Furthermore, what is considered Critical Infrastructure is often a complex discussion, with varying opinions across audiences. Traditional Critical Infrastructure included power stations, water, sewage pump stations, gas pipe lines, power grids and a new entrant, the "internet of things" . This list is not complete and a constant challenge exists in identifying Critical Infrastructure and its interdependencies. The purpose of this research is to highlight the importance of protecting Critical Infrastructure as well as proposing a high level framework aiding in the identification and securing of Critical Infrastructure. To achieve this, key case studies involving Cyber crime and Cyber warfare, as well as the identification of attack vectors and impact on against Critical Infrastructure (as applicable to Critical Infrastructure where possible), were identified and discussed. Furthermore industry related material was researched as to identify key controls that would aid in protecting Critical Infrastructure. The identification of initiatives that countries were pursuing, that would aid in the protection of Critical Infrastructure, were identified and discussed. Research was conducted into the various standards, frameworks and methodologies available to aid in the identification, remediation and ultimately the protection of Critical Infrastructure. A key output of the research was the development of a hybrid approach to identifying Critical Infrastructure, associated vulnerabilities and an approach for remediation with specific metrics (based on the research performed). The conclusion based on the research is that there is often a need and a requirement to identify and protect Critical Infrastructure however this is usually initiated or driven by non-owners of Critical Infrastructure (Governments, governing bodies, standards bodies and security consultants). Furthermore where there are active initiative by owners very often the suggested approaches are very high level in nature with little direct guidance available for very immature environments.
Keywords: Computer crimes -- Prevention; Computer networks -- Security measures; Computer crimes -- Law and legislation -- South Africa; Public works -- Security measures